2015
DOI: 10.15407/cryo25.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of mammalian erythrocytes affects their sensitivity to mechanical stress

Abstract: Реферат: Исследована чувствительность эритроцитов человека, быка, крысы и лошади к действию механического стресса в средах, содержащих 0,15, 0,4 и 0,6 моль/л NaCl. Механический стресс эритроцитов млекопитающих в среде, содержащей 0,15 моль/л NaCl, приводит к потере клетками К + от 30% для эритроцитов лошади до 60% для клеток быка. Максимальную устойчивость по показателю гемолиза к действию механического стресса проявляют эритроциты быка и лошади в среде, содержащей 0,15 моль/л NaCl. Показано, что обезвоживание… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
1
0
1
Order By: Relevance
“…The centrifugal forces might not be high enough under isotonic conditions to induce cation leaks. However, at higher tonicities, these forces may cause cation leaks at lower onsetting tonicity -an inference consistent with the study by Shpakova et al, 88 which showed mechanically induced cation leaks and post-hypertonic lysis at lower tonicities when compared to mechanically unstimulated RBCs. The detrimental aspect of temperature is less obviously linked to the activation of ion transport pathways.…”
Section: Broader Cryobiological Significancesupporting
confidence: 89%
See 2 more Smart Citations
“…The centrifugal forces might not be high enough under isotonic conditions to induce cation leaks. However, at higher tonicities, these forces may cause cation leaks at lower onsetting tonicity -an inference consistent with the study by Shpakova et al, 88 which showed mechanically induced cation leaks and post-hypertonic lysis at lower tonicities when compared to mechanically unstimulated RBCs. The detrimental aspect of temperature is less obviously linked to the activation of ion transport pathways.…”
Section: Broader Cryobiological Significancesupporting
confidence: 89%
“…94,97 Regarding the identification of the HICCs involved in the RVI response of human RBCs, a study revealing that mechanical stress applied to RBCs induces cation leaks in isotonic and anisotonic media should be mentioned. 88 This observation supports the mechano-sensitivity of cation channels hypothesized to be involved in cation leaks and post-hypertonic lysis. Many ion channels exhibit mechanosensitivity.…”
Section: Identification Of the Ion Transport Pathways Involved In The...supporting
confidence: 74%
See 1 more Smart Citation
“…Гемоліз еритроцитів росте з часом під дією механічного стресу (рис. 1), що свідчить про зростання ступеня пошкодження клітин [10]. Для контрольних еритроцитів людини не зареєстровано достовірної різниці у механічній стійкості еритроцитів у середовищі Олсвера та розчині маніту (рис.…”
unclassified